Trends in the Collaboration Pattern of Moroccan Research in Earth Sciences from 1984 to 2019: A Case Study - Fida Medina (European Scientific Journal, ESJ, 2021)
The output of the Moroccan researchers in Earth sciences and their collaboration trends were studied for the period 1984-2019 using the example of the Journal of African Earth Sciences, the preferred journal of this community, and by using simple bibliometric indicators such as collaboration rate and collaboration level. The main results of the study are: (1) Moroccan researchers participated in 253 articles among which, only 12 were singleauthor papers. Multi-authorship is the rule with a mode of 4 authors per paper for 45 articles; (2) the number of authors reached 1251 in all papers. When only international collaboration is considered, 1051 authors are found, from which about 48% are from Morocco and 52% belong to other 31 countries; (3) International collaboration, which was exclusively with French researchers and institutions until the 1990s, grew in number but declined in share to 33- 42% in the last 15 years, while collaboration with other countries became more important because of the internationalization of research programs.